Mulheres filósofas: um silêncio institucionalizado - Peinhopf, Anna Deyse Rafaela (2020)
In this dissertation, we investigate if there is a silence of women philosophers in the History of Philosophy. Considering the pecheutin’s Discourse Analysis, we want to understand the Discursive Formation of Philosophy, which thought and delimited what to be a woman for the centuries, and “authorized” the places that could be occupied by them. So, we have as general objective the analysis of the Philosophy Graduation’s ementaries, at the baccalaureate or undergraduate level, to propose a gesture of analytical reading about some of the meaning effects produced by the Patriarchal Ideological Formation that goes through the Discursive Formation of Philosophy. We want to reflect on the institutionalization of knowledge that, from an Imaginary Formation, which designates what a discipline is, through subjects and themes to be treated. We also investigate whether this process of disciplining knowledge, institutionalizing it, functions as a mechanism that silences women philosophers, deleting their participation as knowledge producers and silencing their works as they are little used in references or do not appear in processes of denomination and referencing of a discipline